Trial-centeredness doctrine: Material Connotations and Methods to Accomplish. (2nd January 2016) - Zhang, Jianwei
Abstract : "Trial as Centrality" has become a widely known phrase due to the current wave of judicial system reform. Trial-centeredness doctrine yet implies considerably various connotations than which the judicial organs interpret as "focusing on court trials." This article endeavors to explain the corresponding nexus between the trial-centeredness doctrine and the procedural phases theory, to disclose the buried causes of why the centrality of trial is shrunk as "merely making trials itself centered in criminal proceedings, " to unfold the reason why the materiality has to be strengthened, and to deeply explore how the investigation centeredness phenomena structurally forms. Moreover, after analyzing a variety of factors relevant to the materiality of trial process, involved in the trial as centrality reform, this article points out that to make criminal trial genuine other procedural reform still has to be launched at the same time, such as promoting the mere prosecutorial information doctrine and etc. Otherwise, trial as centrality reform might hardly persist long nor stand firmly.